A Snapshot on MRSA Epidemiology in a Neonatal Intensive Care Unit Network, Palermo, Italy - Geraci, Daniela M.; Giuffrè, Mario; Bonura, Celestino; Graziano, Giorgio; Saporito, Laura; Insinga, Vincenzo; Rinaudo, Grazia; Aleo, Aurora; Vecchio, Davide; Mammina, Caterina; , The NICU Surveillance Study Group; Ciofalo, Amalia; et al. (Frontiers in Microbiology, 2016)
Objectives. We performed a one-year prospective surveillance study on MRSA colonization within the five NICUs of the metropolitan area of Palermo, Italy. The purpose of the study was to assess epidemiology of MRSA in NICU from a network perspective. Methods. Transfer of patients between NICUs during 2014 was traced based on the annual hospital discharge records. In the period February 2014 – January 2015, in the NICU B, at the University teaching hospital, nasal swabs from all infants were collected weekly, whereas in the other four NICUs (A, C, D, E) at four week-intervals of time. MRSA isolates were submitted to antibiotic susceptibility testing, SCCmec typing, PCR to detect lukS-PV and lukF-PV (lukS/F-PV) genes and the gene encoding the toxic shock syndrome toxin (TSST-1), multilocus variable number tandem repeat fingerprinting (MLVF) and multilocus sequence typing (MLST). Results. In the period under study, 587 nasal swabs were obtained from NICU B, whereas 218, 180, 157 and 95 from NICUs A, C, D and E, respectively. Two groups of NICUs at high prevalence and low prevalence of MRSA colonization were recognized. Overall, 113 isolates of MRSA were identified from 102 infants. Six MLVF types (A-F) were detected, with type C being subdivided into five subtypes. Five sequence types (STs) were found with ST22-IVa being the most frequent type in all NICUs. All the MRSA molecular subtypes, except for ST1-IVa, were identified in NICU B. Conclusions. Our findings support the need to approach surveillance and infection control in NICU in a network perspective, prioritizing referral healthcare facilities.